The influence of competence on attitude of success Bumiputera entrepreneur (SEDC, Kuching Sarawak) / Alfitri Abdul Rahman... [et.al] - Abdul Rahman, Alfitri; Bollhassan, Husnul Muassyarah (2017)
By the coming 2020, the entrepreneurial sector is the most important sector that will have a major impact on Malaysia. And as a growing nation, Malaysia intends to improve the living and economic standards of the population in every place, including in Sabah and Sarawak. In Sarawak, various central and state government agencies have been entrusted to ensure Sarawak's Bumiputera economy is comparable to other races. SEDC is one of the agency that been set up by the Sarawak State Government to assist the local entrepreneur. One of the criteria of a successful person is, to have good attitudes and behaviors. Attitude is one of the prime mover that makes a person successful or not. Attitudes that are always positive and constantly improve their weakness are the key to the development of an entrepreneur's self. That is why one of the criteria of a successful person must have good attitudes and behaviors. Therefore, this study is conducted to find the influence of this entrepreneur competencies to the attitude of successful entrepreneur. The study is aim to answer this main question. Based on survey conducted to 70 respondents the study disclose that, there is a relationship between skills, goals, and financial management to the attitudes of success entrepreneur. These findings suggest that to be successful Bumiputera entrepreneur should pay more attention, equip and acquired them self with more skills to face the market stiff competitiveness, to have the entrepreneurial mindset and understand the financial management.